Pembaharuan Pendiidkan Islam - Mardinal Tarigan; Rosalinda Amanda Sari; Hafidzah Nurul Ilmi (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
The update in Islamic education is a crucial response to the evolving dynamics of social, technological, and cultural aspects. This article explores the concept of modernization within the context of Islamic education, emphasizing the importance of maintaining the relevance of religious values while embracing advancements in science and technology. The discussion encompasses the scope of Islamic education, aiming to nurture individuals who are devout and of high quality, along with research methodologies adopting a literature review approach. Furthermore, the article analyzes the understanding, scope, and teaching methods in Islamic education, as well as the background of educational reforms in Indonesia. The research concludes that the modernization of Islamic education presents both challenges and opportunities in maintaining its relevance amidst changing times.